2022
DOI: 10.1155/2022/8495451
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Point Results of Dynamic Process Dˇϒ,μ0 through FIC‐Contractions with Applications

Abstract: This article constitutes the new fixed point results of dynamic process D(ϒ, μ0) through FIC-integral contractions of the Ciric kind and investigates the said contraction to iterate a fixed point of set-valued mappings in the module of metric space. To do so, we use the dynamic process instead of the conventional Picard sequence. The main results are examined by tangible nontrivial examples which display the motivation for such investigation. The work is completed by giving an application to Liouville‐Caputo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ćirić [3] demonstrated that fixed points exist uniquely for generalized contraction mappings in a metric space, provided that the mapping exhibits orbital continuity. Ali et al [4] discussed the dynamic process through integral contractions of the Ćirić kind. Anevska et al [5] provided proofs for some fixed-point results in 2-Banach spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Ćirić [3] demonstrated that fixed points exist uniquely for generalized contraction mappings in a metric space, provided that the mapping exhibits orbital continuity. Ali et al [4] discussed the dynamic process through integral contractions of the Ćirić kind. Anevska et al [5] provided proofs for some fixed-point results in 2-Banach spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Branciari [1] analyzed the existence of FPs for mappings defined on complete MS and focused on a general contraction of integral-type. For additional information, refer to [2,3]. Nadler [4] introduced a novel approach to FP theorems, contributing to the expansion of the BCP and incorporating multivalued mappings within complete MS.…”
Section: Introductionmentioning
confidence: 99%